2013
DOI: 10.1016/j.jss.2012.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism during the early “flow phase” after burn injury

Abstract: Background Burn injury (BI) is associated with insulin resistance and hyperglycemia which complicate clinical management. We investigated the impact of BI on glucose metabolism in a rabbit model of burn injury using a combination of PET and stable isotope studies under Euglycemic Insulin Clamp (EIC) conditions. Materials/Methods Twelve male rabbits were subjected to either full thickness burn injury (B) or sham burn (SB). Three days after treatment, an EIC condition was established by constant infusion of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To this end, in addition to immune dysfunction, burn patients also experience severe metabolic dysregulation, characterized by elevated basal metabolic rate and a paradoxical comingling of hyperglycemia and hyperinsulinemia. [17][18][19][20][21] Similarly, several animal studies have demonstrated altered metabolism in animal models of burn injury, including insulin resistance and hyperglycemia. [21][22][23] The relationship between metabolism and immunity has been focus of much recent research activity.…”
Section: Burn Injury Generates Numerous Inflammatory Stimuli Includingmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, in addition to immune dysfunction, burn patients also experience severe metabolic dysregulation, characterized by elevated basal metabolic rate and a paradoxical comingling of hyperglycemia and hyperinsulinemia. [17][18][19][20][21] Similarly, several animal studies have demonstrated altered metabolism in animal models of burn injury, including insulin resistance and hyperglycemia. [21][22][23] The relationship between metabolism and immunity has been focus of much recent research activity.…”
Section: Burn Injury Generates Numerous Inflammatory Stimuli Includingmentioning
confidence: 99%
“…[17][18][19][20][21] Similarly, several animal studies have demonstrated altered metabolism in animal models of burn injury, including insulin resistance and hyperglycemia. [21][22][23] The relationship between metabolism and immunity has been focus of much recent research activity. 24,25 Insulin receptor signaling suppresses TLR expression in human granulocytes, 26 and hyperglycemia perturbs both cytokine secretion and TLR signaling in myeloid cells.…”
Section: Burn Injury Generates Numerous Inflammatory Stimuli Includingmentioning
confidence: 99%
“…After severe burn, the stress process is followed and represented by the release of a large amount of stress-related hormones and cytokines. This stress process leads to mal-metabolism of carbohydrates via insulin resistance and hyperglycemia [ 28 ]. For a very long time, researchers and clinical practitioners have considered hyperglycemia post severe burn as a type of stress-related phenomena and quite different from diabetes.…”
Section: Discussionmentioning
confidence: 99%